Do Crime-Prone Areas Attract Gambling Shops? A Case of London Boroughs - Kumar, Pradeep
We investigate a causal effect of crime on the number of betting shops by using annual data from London boroughs (2007-2015). Using an instrumental variable strategy, we estimate a panel model accounting for omitted variables and borough-level heterogeneity. Our estimation results show that a 1% increase in crime rate causes a 1.2% increase in the number of betting shops (per capita). Put differently, a new betting shop opens in a borough for every 1.4% increase in the local crime rate, on average. The causal effect is robust across a variety of specifications, although the magnitude varies across models